2002
DOI: 10.4315/0362-028x-65.5.806
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Foodborne Paenibacillus and Bacillus spp. against Clostridium botulinum

Abstract: The saprophytic Paenibacillus and Bacillus spp. found in cooked chilled foods may have an effect on the growth of Clostridium botulinum, a major microbiological hazard, especially for pasteurized vacuum-packaged products. Culture supernatants of 200 strains of Paenibacillus and Bacillus strains isolated from commercial cooked chilled foods containing vegetables were screened for activity against C. botulinum type A, proteolytic type B, and type E strains in a well diffusion assay. Nineteen strains were positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…One limiting factor is the strong competition or even inhibiting effect by other bacteria (Smith, 1975; Girardin et al, 2002). Studies of marshland sediments have demonstrated inhibition of C. botulinum type C by other bacteria, including Bacillus licheniformis , Bacillus mycoides/cereus , Streptococcus spp., and Clostridium spp.…”
Section: Conditions Preventing Botulism Outbreaksmentioning
confidence: 99%
“…One limiting factor is the strong competition or even inhibiting effect by other bacteria (Smith, 1975; Girardin et al, 2002). Studies of marshland sediments have demonstrated inhibition of C. botulinum type C by other bacteria, including Bacillus licheniformis , Bacillus mycoides/cereus , Streptococcus spp., and Clostridium spp.…”
Section: Conditions Preventing Botulism Outbreaksmentioning
confidence: 99%
“…This antimicrobial activity of P. polymyxa referred to the production of antimicrobial peptides. The other important thing is that fungi and a wide range of Gram-positive and Gram-negative bacterial cultures, such as Escherichia coli , Streptococcus mutans , Leuconostoc mesenteroides , and Bacillus subtilis , were sensitive to the antimicrobial peptides produced by P. polymyxa [13, 14]. The combinations of different cellulolytic and hemicellulolytic bacteria in SSF might lead to the production of different types of enzymes at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…1998; Seldin et al. 1999) and even important anaerobic pathogens as Clostridium botulinium (Girardin et al. 2002).…”
Section: Introductionmentioning
confidence: 99%